Evidence for Surface Faulting Earthquakes on the Montereale Fault System (Abruzzi Apennines, Central Italy). Issue 9 (1st September 2018) - Cinti, F. R.; Civico, R.; Blumetti, A. M.; Chiarini, E.; La Posta, E.; Pantosti, D.; Papasodaro, F.; Smedile, A.; De Martini, P. M.; Villani, F.; Pinzi, S.; Pucci, S.; et al.
Abstract: We conducted paleoseismic studies along the Montereale fault system (MFS; central Italy). The MFS shows geomorphological evidence of Late Quaternary activity and falls within the highest seismic hazard zone of central Apennines, between the epicentral areas of two recent earthquake sequences: 2009 L'Aquila and 2016–2017 central Italy. We excavated two trenches along the San Giovanni fault splay of the system, one intercepting the N140° striking bedrock main fault plane and the other cutting two subparallel fault scarps on the colluvial/alluvial deposits on the fault hanging wall. Excavations revealed repeated fault reactivation with surface faulting in prehistorical and historical times. We recognized and dated seven events in the last 26 kyr. The most recent ground‐rupturing event (evb1) possibly occurred 650–1, 820 AD, consistent with one of the three main shocks that struck the area in 1, 703 AD. A previous event (evb2) occurred between 5, 330 bc and 730 bc, while older events occurred at 6, 590–5, 440 bc (evb3), 9, 770–6, 630 bc (evb4), and 16, 860–13, 480 bc (evb5). We documented two older displacement events (evb7 and evb6) between 23, 780 bc and 16, 850 bc . The minimum vertical slip rate at the trench site in the last 28–24 kyr is 0.3–0.4 mm/year. The inferred average recurrence interval for surface‐faulting events along the MFS is no longer than ~4 kyr. Based on the surface fault length ranging between 12 and 20 km, earthquakes with ≥ M 6.0 are possible for the MFS. The MFS is an independent earthquake source, and its paleoseismic data are fully comparable with those known for faults in central Apennines. Key Points: Seven earthquakes ruptured the Montereale fault system (central Italy) since 26 kyr First estimates of the Montereale fault parameters: length, earthquake recurrence, and slip rate The Montereale fault system is an individual earthquake source within the central Apennines seismogenic belt (Italy)